Curricular strategy of Natural and Traditional Medicine in the Comprehensive Dentistry Discipline - Vivian Guillaume Ramírez; Teresita de Jesús Clavera Vázquez; María Estrella Marín Quintero; Yadira Montenegro Ojeda; Maria Luisa Novoa Lirio (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Natural and Traditional Medicine constitutes a necessary formative area according to the Professional Framework of the future graduate students in Dentistry.  It is defined as a curricular strategy in the current curriculum according to "D" plan, in which the main integrative discipline, Comprehensive Dentistry, is the focal point in the student´s formation. Objective: To describe the curricular strategy of Natural and Traditional Medicine in the Comprehensive Dentistry Discipline. Material and Methods: A descriptive research, with document analysis was carried out. The documents reviewed were: the curriculum in Dentistry; curricular strategies with an emphasis on Natural and Traditional Medicine; the disciplines of Dentistry, in greater detail of Comprehensive Dentistry, and their subjects. Results: The contents on NTM were included in the dental curriculum according to "C" plan. The current "D" plan maintains and improves them, when establishing the NTM as one of the curricular strategies, which presents topics that are expected to be covered in 16 of the 20 subjects of Comprehensive Dentistry as the main discipline. A lack of coincidence among the documents related to the implementation of the strategy was observed. Conclusions: The curricular strategy of NTM in the Comprehensive Dentistry Discipline establishes contents to develop in a high number of subjects of Comprehensive Dentistry as the main discipline, with an integration of conventional dental practices, although a lack of coincidence was perceived among the documents related to the implementation of this work. Keywords. Curricular strategy, Natural and Traditional Medicine, Comprehensive Dentistry, curriculum, curricular discipline.